EVALUATION OF PHYSICAL GROWTH AND NUTRITIONAL STATE OF SCHOOL CHILDREN FROM "CREMAÇÃO" CHILDISH EDUCATION UNIT -BELÉM, PARÁ, BRAZIL- A CASE STUDY. (Fiep Bulletin - online, 2011)
This research aims to register and to evaluate anthropometric measures of school children from Cremação Childish Education unit of SEMEC, Belém. It is a case study realized with 157 children of both sexes, aged from 1 year and 11 months up to 5 years and 1 month of age. For verification of body weight, it was used a balance with digital portable platform, with capacity of 100 kg, with 100 grams precision and a undeformable measure tape, with subdivision 0.1 'cm, to verify the stature. The stature, age and date of birth data were transferred to the electronic means via software Whoantro-2006/WHO. For nutritional status classification it was used as reference child growth curves proposed by WHO (WHO, 2006). According to the results, it was identified adequacy of stature to age focused on 92.99% of children present and 6.37% of children with short stature. The weight index for age observed had determined that 94.26% of children show age appropriate to weight.
Keywords: Nutritional evaluation; Physical Growth and Stature